2011
DOI: 10.1208/s12249-011-9615-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Testing of Sublingual Tablets: A Novel In Vitro Method

Abstract: Abstract. In the sublingual (SL) cavity, compared with the gastrointestinal tract, tablets are subjected to minimal physiological agitation, and a limited volume of saliva is available to facilitate disintegration and dissolution. None of the official compendial dissolution apparatuses and methods simulate these SL conditions. In this study, a custom-made dissolution apparatus was constructed, and a novel in vitro method that simulates SL conditions was evaluated. Several epinephrine 40 mg SL tablet formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…These RDSTs contained no lactose or bisulfite and were quality control tested for tablet weight variation, content uniformity and friability using the harmonized United States Pharmacopoeia (USP) standards and criteria [23,24]. Tablet disintegration time was measured using a previously developed in‐vitro disintegration test to simulate the sublingual environment [18–21]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These RDSTs contained no lactose or bisulfite and were quality control tested for tablet weight variation, content uniformity and friability using the harmonized United States Pharmacopoeia (USP) standards and criteria [23,24]. Tablet disintegration time was measured using a previously developed in‐vitro disintegration test to simulate the sublingual environment [18–21]…”
Section: Methodsmentioning
confidence: 99%
“…[23,24] Tablet disintegration time was measured using a previously developed in-vitro disintegration test to simulate the sublingual environment. [18][19][20][21] Adrenaline content was analysed using a reverse-phase HPLC system with ultraviolet detection (Waters Corp., Milford, MA, USA) according to the USP method for Epi injections. [25] In-vivo studies…”
Section: Manufacturing and Quality Control Of Tabletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we developed Epi RDSTs that retain sufficient hardness to withstand shipping and handling but disintegrate rapidly (≤30 s) to release Epi (12)(13)(14)(15)(16). In a validated rabbit model, we demonstrated that the rate and extent of absorption after administration of an Epi 40 mg RDSTs was similar to the rate and extent of absorption after administration of Epi 0.3 mg intramuscular (IM) through an EpiPen the sublingual mucosa and achieve the required plasma epinephrine levels.…”
Section: Introductionmentioning
confidence: 84%
“…It is reasonable to have an in vitro method of testing dissolution that is sensitive to formulation factors that affect the solubility process and therefore, bioavailability. In recent years, the discriminatory capabilities and reliability of dissolution tests of tablets have attracted much attention [30] . In order to establish acceptance criteria and preview how alterations in manufacturing would affect bioavailability, different parameters were used to differentiate and identify the differences in formulations.…”
Section: Dissolution Of Drug-loaded Tabletsmentioning
confidence: 99%